End-to-end cost assessment of large particle private-wire services - Minfeng ZHANG; Nan ZHOU (Dianxin kexue)
With the bandwidth of private-wire going up,end-to-end cost assessment of large particle private-wire service becomes more important.Based on the end-to-end bearer form and economic evaluation theory,a cost assessment model was presented,and supplemented by case analysis.Main equipment,pipes,cables,equipment room and other costs were takes into account comprehensively.The total annual cost of large particle private-wire service can be accurately evaluated and operators’ pricing can be guided.